Hitting Where It Hurts Most: COVID-19 and Low-Income Urban College Students - Núria Rodríguez-Planas (Institute of Labor Economics (IZA), 2020)
Using administrative data merged with a rich student survey collected during the summer of 2020, we document the immediate and short-term educational, financial, and personal burdens of New York city's low-income public university students during the COVID-19 pandemic, the closing of college campuses, and the city's shutdown. Low-income students are identified by whether they ever received the federal Pell Grant. We find that low-income college students were 8% more likely than general students at the same college to experience challenges while attending online classes during spring 2020 mostly due to higher childcare responsibilities, greater lack of internet, or greater probability of being sick or stressed. They were also 11% more likely to consider dropping a course because of concerns that their grade would jeopardize their financial assistance. Despite being 21% more likely to receive financial support from emergency relief grants and stimulus payments and unemployment benefits from the CARES Act, low-income college students have or are currently more at risk of experiencing financial distress including securing basic food needs (46% higher) and shelter (62% higher), facing job loss (15% higher), or losing their financial aid (12% higher). We identify potential mechanisms driving these results and correct for multiple hypothesis testing. Our findings underscore the need to target a variety of services and assistance towards low-income college students to secure their wellbeing and college continuity.
Keywords: I24; I23; I22; 330; COVID-19; low-income; college students; health; educational outcomes; financial support; employment; challenges